Decision-Making Considering Dependence Relations for the Improvement of Production Management - Salomon, Valério; Whitaker, Rozann (Brazilian Journal of Operations & Production Management, 2010)
Traditional Multiple Criteria Decision-Making methods have been effectively applied by Brazilian industries. An intrinsic requirement of applying these methods is that the alternatives and criteria be independent of one another. In this paper we show how a Brazilian company can consider dependencies among the alternatives and among the criteria in solving Production Management problems. The need to consider dependence among alternatives was detected in the course of a study applying traditional decisionmaking methods. The main benefit from considering dependence was the notably higher satisfaction of the decision-makers. That is, it made the decision-making model closer to the real problem, as perceived by the decision-makers. A main conclusion of this article is that considering dependence in decision making can improve the quality of the process.